Sumô - de Carvalho Ribeiro, Pedro Paulo; Jachinto da Cruz, Sérgio; de Souza Lopes, Renato; Donner, Rodolpho; Alves dos Reis, Rodovalho; Leite do Couto, Ronaldo (Revista de Educação Física / Journal of Physical Education, 2020)
[...]